Collaborative Course Design: A Contribution Toward a Radical Food Systems Pedagogy - Classens, Michael; Gericke, Nadia; Digout , Amara; Fisher, Aden; Frechette, Madeleine; Wong, Christina (Radical Teacher, 2025)
The nascent (sub)field of critical food systems pedagogy is developing, in part, through a critique of conventional approaches to teaching and learning about food and agriculture. Within this fertile context, scholars and practitioners have been reckoning with what and how to teach for more just and sustainable worlds through a distinctly critical food systems pedagogy. We draw inspiration from this work, and build on it through experimentation with how we design what we teach. Our specific, modest intervention focuses on engaging students, in conversation, in the process of curriculum co-design. We explore this through a case study of co-designing The Edible Campus, a combined 4th year and graduate level course. We provide insight into the co-design process, outline how the co-design process shaped the course, and summarize challenges of the co-design process.